PERAN THE UNITED NATIONS CHILDREN’S EMERGENCY FUND (UNICEF) DALAM MENGATASI PERDAGANGAN ANAK DAN EKSPLOITASI SEKSUAL DI BELGIA TAHUN 2008-20012 - Ika Yunika Irmalita; Try Joko Waluyo (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2015)
This research explains about how the UNICEF’s rule as international organization in overcoming child trafficking and sexual exploitation in Belgium (2008-20012). Child Trafficking is the one of international politic issues that abuses Human Rights especially for children. Belgia is favorite destination for child trafficking and sexual exploitation activity. UNICEF as international organization was established on september, 11th 1946 and heartquarters in New York. It’s main purpose is to advocate children’s rights. This reseacrh used qualitative methodhs. In this research, the data was collected by using library research technique where this technique is collecting data sources from the literarture, like books, website official publications, new paper and journal.This research uses pluralism approach which this approach has assumtion that actor international relation isn’t just a state but there’s another actor one of international organization. In this research, writer uses International Organization Theory which each organization has their duty. This research of UNICEF has important duties and roles to overcome child trafficking and sexual exploitation in Belgium.To overcome this clild trafficking and sexual exploitation in Belgium. UNICEF has more rules in education aspects. It’s because with the education which is implemented well for next generation in Blegium, so hopefully Belgium will have competence human resource and it’s also will rduce proverty here.Keywords : UNICEF, child trafficking, sexual exploitation, Belgium.